Fiinite element analysis on multi-plane defects of ASTM 106 steel pipe - Cheong, Kok Soon (2013)
The predictions of pipeline burst pressure in the early stage are very important as the failure of pipelines can result in damage to the environment, injury to the public and high repair costs. Therefore, the accurate detection and characterization of defects in pipelines are of high interest, in particular to give a better understanding of possible failure modes and probabilities for a pipeline. This thesis deals with the study on the effect of multi-plane defects of ASTM 106 steel pipe. The objectives of this project are to determine the burst pressure of detective pipe and to analyses the effect of different planes defect on burst pressure. This project implicates analysis of the ASTM 106 steel by using MSC Patran 2008 r1 software as pre-processor and MSC Marc 2008 r1 software as a solver. A quarter of pipe was simulated by fully applying the symmetrical condition. The pipe is modeled in 3-D with outer diameter 381 mm, wall thickness of 17.5 mm and different defect parameter. In this analysis, stress modified critical strain (SMCS) and von Mises used as failure criterion to predict the failure defective pipe. Results show that the burst pressure decrease when decreasing in multi defect planes thickness. The defect thickness appears as a most influence parameter that affects the burst pressure. However, the defect width has insignificant effect to the burst pressure. The results have been compared to von Mises stress burst prediction method. From the results, stress modified criteria strain (SMCS) gives the higher values compared to von Mises